Understanding Predictors of Violent and Non-Violent Crime Victimization among Asian-American/Pacific Islanders - Lee, Jin R. (Victims & offenders, 2023)
Violent crimes targeting the Asian-American/Pacific Islander (AAPI) community has increased since the beginning of the COVID-19 pandemic. While Anti-Asian violence existed before the pandemic, few have examined the predictors of AAPI crime victimization. Given this gap in the literature, the current study examined the factors that predicted violent and nonviolent crime victimization using a sample of 342 victimization incidents from 292 individuals self-identified as AAPI in the 2019 National Crime Victimization Survey (NCVS). The implications of this analysis for our understanding of AAPI victimization will be discussed in detail, along with future directions for research involving anti-Asian racism and violence.